IMPROVING THE STUDENTS WRITING ABILITY IN ARGUMENTATION PARAGRAPH THROUGH TEAM ASSISTED INDIVIDUALIZATION - Setiadi, Muhammad Astrianto; Nurfayanti, Rezky; Nurfayanti, Rezky (EXPOSURE : JURNAL PENDIDIKAN BAHASA DAN SASTRA INGGRIS, 2016)
This research aimed at explaining the improvement of the studentsâ Writing ability in writing component of organitation and writing component of content. To explain the improvement, the researcher used a Classroom Action Research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the eleventh grade students of SMA Negeri 1 Bontonompo Selatan with the number of the subject 30 students with 20 women and 10 men. Instruments are test and observation. The findings of the research were the result of studentsâ mean score in organization was 50 after evaluation in cycle I it became 63.16 data source (D-Test) it became 78.16 % D-testÂ in cycle II, the studentsâ mean score of content was 50,93 after evaluation in cycle I it became 64.16 and it became 79 in cycle II. The studentsâ observation was 67.5 % in cycle 1 and it became 82.5 % in cycle 2. It means that Team Assisted Individualization Â is one of the effective teaching strategies for the eleventh grade students at SMA Negeri 1 Bontonompo Selatan to improve their writing ability in Argumentation paragraph.Â Keywords: Team Assited Individualiation, Writing, Argumentation Paragraph, Students